Jim Gaffigan [videorecording (DVD)] : beyond the pale - Gaffigan, Jim; Drumm, Michael (Director) (Image Entertainment, 2005)
The unhippest guy in the room is going to crack you up. Jim Gaffigan is the nice guy next door- with more than a hint of the devil in him. A regular of The Ellen Show and That '70s Show, the versatile actor shows his unique style of humor.